Inclusive and Sustainable Industrialization in the Future Global Development Agenda - Kim, Jim Yong (2016)
Remarks delivered by Jim Yong Kim, President of the World Bank Group discuss the critical role of inclusive and sustainable industrialization in the future global development agenda, including to end extreme poverty by 2030. He speaks about working with UNIDO and the government of Ethiopia to ensure that new industrial parks make use of recycled water and renewable resources, develop green areas, and reflect upgraded environment standards and environmental inspection systems. The World Bank Group is looking for opportunities to work closely with UNIDO on industrial zones in Senegal.